2022
DOI: 10.3389/fvets.2022.833346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycopene on the Growth Performance, Antioxidant Enzyme Activity, and Expression of Gene in the Keap1-Nrf2 Signaling Pathway of Arbor Acres Broilers

Abstract: The objective of this study was to determine the effect of dietary lycopene supplementation on the growth performance, antioxidant enzyme activity of serum and liver, and gene expressions associated with Kelch-like ech-associated protein-1 (Keap1)/Nuclear Factor E2-related factor 2 (Nrf2) pathway in liver of Arbor Acres broilers. A total of 288 1-day-old male broilers were randomly divided into 4 treatments with 6 replicates and 12 chickens for each replicate. The control group was fed with the basal diet, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Wang et al. (2022) found that adding 30 mg/kg LYC to the diet resulted in a decrease in the feed‐to‐weight ratio of 42‐day‐old AA broilers. In this experiment, the addition of 200 mg/kg LYC mitigated the negative impact that AFB 1 had on the performance of the broilers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al. (2022) found that adding 30 mg/kg LYC to the diet resulted in a decrease in the feed‐to‐weight ratio of 42‐day‐old AA broilers. In this experiment, the addition of 200 mg/kg LYC mitigated the negative impact that AFB 1 had on the performance of the broilers.…”
Section: Resultsmentioning
confidence: 99%
“…(2022) found that the addition of LYC could upregulate the mRNA levels of Nrf2 and the protein levels of Nrf2 and downregulate the mRNA and protein levels of Keap1. The dietary inclusion of LYC improved antioxidant status by increasing GSH‐Px and GST activities in the serum and liver (El‐Sheshtawy et al., 2021; Wang et al., 2022). Similarly, we found that 100 µg/kg AFB 1 added to the diet significantly reduced GSH‐Px activity, and a decline in the free‐radical scavenging abilities of ABTS ·+ and OH · was observed, whereas the addition of LYC reversed the decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the eggs produced would be healthier for consumption due to their low cholesterol levels, helping to overcome the phobia associated with high cholesterol concentrations. Furthermore, enriching the diet of hens with tomato waste had no adverse effect on their health; on the contrary, tomato waste showed health-promoting effects, as it contains high concentrations of lycopene, acting as an antioxidant (Wang et al, 2022). Some studies showed that supplementation of laying hens' feed with tomato waste at concentrations of 9-12% reduced egg-yolk cholesterol and improved its colour (Habanabashaka et al, 2014;Mahata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly effective in removing reactive oxygen species (ROS), particularly singlet oxygen [25]. Lycopene is beneficial for enhancing growth responses in broiler chickens exposed to heat stress [2,26,39]. Lycopene's health benefits may be linked to its antioxidant properties, which enhance the numerous physiological reactions in broiler chickens [20,35].…”
Section: Introductionmentioning
confidence: 99%